KEANEKARAGAMAN ZOOPLANKTON DI RAWA BANJIRAN DESA SEDANG KECAMATAN SUAK TAPEH KABUPATEN BANYUASIN - Indah Anggraini Yusanti; Tri Widayasti; Ramadhan Ramadhan (Biota, 2018)
The purpose of this research is to determine the diversity of zooplankton in the swamp flood waters in Sedang Village, Subdistrict Suak Tapeh, District Banyuasin. This research was conducted in Juli in the swamp flood waters in Sedang Village, Subdistrict Suak Tapeh, District Banyuasin. Determination of sampling stationsbased on purposive random sampling. Sampling of fitoplankton was done in 3 stations, they are: Swamp Nebong Kuning (station 1), Swamp Poron (station 2) and Swamp Banan (station 3). Based on the results of the research was found that the type of zooplankton in swamp flood waters in Sedang Village, Subdistrict Suak Tapeh, District Banyuasin consist of 3 classes, they are Monogonota, MastigophoradanCiliata.  Diversity index of zooplankton species in the swamp flood waters in Sedang Village, Subdistrict Suak Tapeh, District Banyuasin in Swamp Nebong Kuning was medium, whereas in the Swamp of Poron and the Swamp of Banan was low.